Self-perception of drug abusers and addicts and investigators’ perception of etiological factors of psychoactive drug addiction - Brajević-Gizdić, Igna (Array, 2009)
Abstract: The aim of this study was to compare investigators’ perception of three most important etiological factors for drug addiction and drug abuse with the self-perception of heroin addicts and drug abusers who used cannabis products and/or ecstasy. The study included 207 heroin addicts (mean age, 26.7 ± 5.8 years) and 238 drug abusers (mean age, 19.3 ± 1.9 years). Each study participant selected the three most important etiological factors for drug addiction or drug abuse from the list in the Pompidou questionnaire according to his or her perception. An investigator also selected the three most important etiological factors for drug addiction or abuse according to his or her perception for each study participant. The self-selected factors were compared with those selected by the investigators.